Process for the Preparation of Artificial Analog of Sanbornite–Glass Composites - Jacob Hormadaly; Mariana Dov; Lonia Friedlander; Natalia Pears (Ceramics)
Barium silicates have been investigated as high-expansion components of solid oxide fuel cells (SOFCs) and, therefore, their synthesis and expansion have been the subject of intensive research in recent years. In this article, we briefly present a new process to make glass–crystalline composites, as well as two novel findings related to a synthesis route of sanbornite (BaSi2O5) and the fast in situ formation of a high-expansion sanbornite composite from a Pyrex-type glass powder. The low-temperature synthesis, composition, and expansion of one type of novel glass composite are described. The composites are made by the reaction of BaCO3 and Pyrex-type powders at 850–950 °C for a short time of one hour. The composites are well sintered and hard, and their linear coefficient of thermal expansion is about 12.3 × 10−6 C−1. The crystalline-phase formation, dilatometer measurements, SEM data, and possible applications of the composites are presented and discussed.